SPORTS MARKETING - Ridvan Ekmekci; Y. Aytul Dgli Ekmekci (Pamukkale University, 2010)
Marketing which is entered to almost our whole life, now more than goods and services, became an important concept of ideas, persons, institutions, events, and facilities. As a main activities of business co. marketing has an important place in sports industry. Recently, the development of special sport marketing strategies and the presentation of sport goods and services to consumers are gaining importance. Efforts of increasing income of sport clubs, because of sport organization popularity, either media or sports business co. started to focus on marketing structure like other business services. Because of definition of sports usage, the term of "Sports Marketing" was used firstly by Advertising Age in 1978 as an increasing presentation tool in industrial merchandise and service marketing. Sport marketing, adapted from general marketing definitions, was defined as " includes arrangement of all activities to meet needs and wants of sports consumers." (Mullin, Hardy, Sutton, 2000:8-9).